Influence of Microwaves on the Water Surface Tension - Parmar, Harisinh Bhikhubhai; Asada, M.; Kanazawa, Y.; Asakuma, Y.; Phan, Chi; Pareek, Vishnu; Evans, G. (American Chemical Society, 2014)
In this study, microwave irradiation was applied to hanging droplets of both water and ethylene glycol. Once the irradiation had ceased and the droplet was allowed to return to its original temperature, it was found that the surface tension of ethylene glycol returned to its original value. In contrast, the water surface tension remained well below its original value for an extended period of time. Similar observations have been reported for magnetically treated water, but this is the first time that such a lasting effect has been reported for microwave irradiation. The effect can be attributed to the unique hydrogen bonds of interfacial water molecules. While the irradiation intensities used in this study are well above those in household devices, there is certainly the potential to apply the methodology to industrial applications where the manipulation of surface tension is required without the use of chemical addition.